61 Outcomes of An Advanced Nurse Practitioner-Led Pops Service in A District General Hospital. (16th March 2021) - Irimia, A M; Tennant, A; Waldron, A; Bashir, N
Abstract: Introduction: There is an increased need for geriatrician input to older adults outside of the medical wards. There is a lack of geriatricians to contribute to these services. An example includes the Proactive care of older people undergoing surgery (POPS) service where geriatricians perform comprehensive geriatric assessment (CGA) to identify comorbidities and geriatric syndromes which may lead to poor post-operative outcomes. Advanced nurse practitioners (ANP) are highly skilled staff members and are increasingly used to provide the POPS service. We wanted to review the outcomes of our Nurse Led POPS service. Methods: Patients aged over 70 admitted as an emergency to upper gastrointestinal and colorectal surgery were assessed by the POPS ANP using CGA. Assessments were completed on a proforma. Data was collected prospectively on a data collection form documenting new issues detected and interventions made. The results were analysed using an Excel spreadsheet. Results: 147 patients were reviewed by the ANP between November 2018 and March 2019. All patients were screened for frailty, cognitive impairment and delirium. 37.41% were clinically frail, 17.72% had cognitive impairment and 11.56% had delirium. New issues were identified in 90.47% of these patients; polypharmacy (80.27%), new catheter (53.74%), weight loss (46.94%), incontinence (36.05%), falls (29.25%) and pain (25.17%). Medical issues were also identified including electrolyte abnormalities (47% patients), acute kidney injury (22% patients), cardiac issues (8% patients) and respiratory problems (7% patients). Additional interventions included stopping medication (27.89%), starting new medication (20.41%), requesting further investigations (97.28%), referring to allied health professionals (95.24%) and advanced care planning (15.65%). Conclusions: A POPS ANP can effectively conduct CGA identifying new medical issues and geriatric syndromes missed by the surgical teams in an acute setting.